India since independence : making sense of Indian politics - Kiruṣṇā Ān̲ant, Vi (Longman, 2010)
India Since Independence: Making Sense of Indian Politics is a comprehensive account of India's post-independence political history. It traces the development of the various political parties in India and places the current political scenario in a historical context. Beginning with a brief review of the intellectual tradition in India in the nineteenth century, it discusses the emergence of Mahatma Gandhi on the national political scene and the role of Indian capitalists in the freedom struggle. With a description of the predominance of the Congress party in the political discourse during the first few decades after independence, the narrative delves deep into the affairs of the party to include the rise of Indira Gandhi, the Congress split of 1969, and the infamous Emergency of 1975. The book then proceeds to the factors that caused the decline of the Congress party, and the formation and the demise of the Janata Party. It also covers political crises manifesting in the unrest in Assam, Punjab, and Jammu and Kashmir; the emergence of regional political parties in various states; the Bofors scandal; and the Ayodhya campaign.